Effects of maltodextrin in freeze drying on the physical and functional properties of different type of milk powder - Alibekov, Ravshanbek Sultanbekovich; Aitbayeva, Aigerim Zhumagalievna; Khamitova, Barna Makhamatovna; Azimov, Abdugani Mutalovich; Sulaiman, Alifdalino; Mustapa Kamal, Siti Mazlina; Taip, Farah Saleena (Informa Healthcare, 2025)
This study examines the impact of maltodextrin concentration (0%-20%) on the physical and functional properties of freeze-dried cow and mare milk powder. Maltodextrin, a common additive in milk powder production, can significantly affects the physical properties of the powder by improving solubility, texture, and prevents clumping. The research aims to evaluates the effects of maltodextrin concentrations on freeze-dried cow and mare milk powder. Samples were prepared by homogenizing fresh milk and adding maltodextrin at various concentrations. The milk was then freeze-dried, and the properties of the resulting milk powder were analyzed. Results show that maltodextrin addition reduced moisture content in both cow and mare milk powders. Bulk and tapped density increased with higher maltodextrin concentrations. The addition of maltodextrin also improved flowability, as indicated by lower Carr Index and Hausner ratio values. Morphological analysis revealed a smoother texture and uniform particle size in freeze-dried milk powder with higher maltodextrin levels. Solubility and foaming capacity also improved, with cow milk generally exhibiting better solubility compared to mare milk. In conclusion, maltodextrin concentration enhances the physical and functional properties of freeze-dried cow and mare milk powders.